Prevalence rate of chronic overuse pain in taekwondo athletes - Koh, J.-O. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to estimate the prevalence of chronic overuse pain (COP) and to identify possible risk factors of COP in sport poomsae taekwondo.